Ivory trade under scrutiny - David Western (Pachyderm)
Notes the release of the ITRG report in June 1989, the almost immediate ivory bans imposed by several consumer states, other studies focused on the ivory trade and elephants which were tabled about the same time and the resulting situation as it stands in late 1989.